Republic of Fiji Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2017)
Fiji is a small island nation in the South Pacific Ocean with population of 870,000.Nevertheless, Fiji has one of the most sophisticated economies among the Pacific Islands. The economy is the second largest in the Pacific after Papua New Guinea, and it is the most industrially advanced, with substantial services and manufacturing sectors.Fiji has not, however, realized its full economic potential.The 2014 election was a turning point for Fiji in many respects. First, the current government was elected with an outright majority and strong cross-ethnic support. Second, the election saw a genuine political debate, with citizens offered a choice between different visions for the future (Frankel 2014). Third, the election, which was declared free and fair by international observers, paved the way for Fiji’s re-engagement with development partners and created a better environment for private investment.Fiji can build on its relatively strong institutions to deliver faster growth and shared prosperity.The government plans to build on its achievements in poverty reduction and shared prosperity. The national development plan is to double real per capita income by 2035.The World Bank’s report Pacific Possible sets out several ideas for accelerating growth in Fiji by 2040. Areas of opportunities include tourism, migration, fisheries, deep sea mining, and the knowledge economy.This Strategic Country Diagnostic (SCD) identifies three pathways, as well as cross-cutting issues. (i) Stronger growth; (ii) Better access to services by all; (iii) Building resilience. These three pathways should be supported by cross-cutting efforts to improve governance, that is, to improve policy and the institutional capacity of the public sector to accelerate progress toward the twin goals.However, it continues to face a number of cross-cutting governance challenges.This report has identified many constraints and many possible policy solutions. But not everything can be done at once: priorities need to be selected. In selecting the priorities, this SCD uses three main criteria. The first is whether a policy is a precondition for making progress in pursuing others. The second is whether a policy is expected to have positive spillovers across different domains (e.g., growth, equity, resilience). The third is whether a policy is feasible, that is, it can be implemented in the medium term given cost, capacity, and political feasibility for action.